Overcoming loss, Muhammad Syafiq Aiman resolves to earn his degree - Siti Nurfarmy, Ibrahim (UMPSA, 2024)
GAMBANG, 26 October 2024 – Never imagining that he would lose a significant figure in his life at the young age of 13, Muhammad Syafiq Aiman Suhirman resolved to change the course of his family’s life.